UPAYA PENCEGAHAN PEMUTUSAN HUBUNGAN KERJA PEKERJA DI SEKTOR FORMAL BERDASARKAN KEADAAN MEMAKSA PANDEMI COVID-19 - Suprantio, Steven (Veritas et Justitia, 2021)
The business world everywhere including those in Indonesia cannot but felt the brunt of economic slowdown caused by the public health emergency (the COVID 19 pandemic). Quite a few national and local businesses have had to close their operation and lay off all its employees. Although the consensus between the government, workers (individuals and unions) as well as employers is to prevent and avoid termination of employment at all costs, the Law No. 11 of 2020, re. Job Creation allows massive dismissal of employees due to economic necessity or state of emergency. This article shall critically examine how the prevailing law, Law No. 11 of 2020 re. Job Creation regulates termination of employment in case of state of emergency.